The Effect of Acupuncture on the Quality of Life in Patients With Migraine: A Systematic Review and Meta-Analysis - Jiang, Yin; Bai, Peng; Chen, Hao; Zhang, Xiao-Yu; Tang, Xiao-Yi; Chen, He-Qing; Hu, Ye-Yin; Wang, Xiao-Li; Li, Xin-Yi; Li, You-Ping; Tian, Gui-Hua (Frontiers in Pharmacology, 2018)
Background: Acupuncture is frequently used as an efficient method to prevent and treat migraines. However, its effect on the quality of life remains controversial. Methods: 7 databases such as PubMed and Cochrane Library were searched to retrieve reference lists of eligible trials and related reviews. Randomized controlled trials that were published in Chinese and English were included. Results: Acupuncture resulted in lower Visual Analogue Scale scores than the medication group at 1 month after treatment (MD -1.22, 95%CI -1.57 to -0.87; low quality) and 1 to 3 months after treatment (MD -1.81, 95%CI -3.42 to -0.20; low quality). Compared with sham acupuncture, acupuncture resulted in lower Visual Analogue Scale scores at 1 month after treatment (MD -1.56, 95%CI -2.21 to -0.92; low quality). Conclusion: Acupuncture exhibits certain efficacy both in the treatment and prevention of migraines, which is superior to no treatment, sham acupuncture and medication. Further, acupuncture enhanced the quality of life more than did medication.